Using the substitution method for systems of equations

skooter

New member
Joined
Sep 1, 2006
Messages
12
Hi it's me again with another one that I'm probably making a simple mistake on :)

x - y = 1
5x + 3y = 45

Using only the substitution method.

here's what I've got:

x - y - y = 1 - y
x = 1-y

5(1-y) + 3y = 45
5-5y + 3y = 45

so -5y + 3y = -2y and 45 - 5 = 40

I think this may be where I'm going wrong. But I am my own teacher w/ only one example in a workbook for a guide

so -2y = 40 or 2y = -40
y = -20

now substituting -20 for y in the first problem:

x - (-20) = 1

x = -19

works great for the first problem but for the second problem...

5(-19) + 3 (-20) = 45

-45 + -60 = -105

and that's how good of a teacher I am for myself :p
 

Denis

Senior Member
Joined
Feb 17, 2004
Messages
1,486
skooter said:
x - y = 1
Using only the substitution method.
here's what I've got:
x - y - y = 1 - y
x = 1-y
x - y + y = 1 + y
x = 1 + y
 

skooter

New member
Joined
Sep 1, 2006
Messages
12
Ty so much

I knew it was something simple this whole time =).
 
Top